KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DAN KETERAMPILAN MENULIS TEKS EKSPOSISI - Afriyanti, Atika; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is three. First, describing reading skills understanding text of class VIII students at SMP Negeri 32 Padang. Second, describing the exposition for writing the text skills of Grade VIII students in Padang Middle School 32 Third, describing the correlation of reading skills in the text comprehension and the exposition for writing text skills for grade VIII students of SMP Negeri 32 Padang. This type of research is quantitative with descriptive method. The design used is correlational design. The study population was grade VIII students of SMP Negeri 32 Padang who were enrolled in the 2018/2019 school year, which was 196 students. The study sample was determined by proportional random sampling of 25% of the population, namely 49 students. The research data is in the form of a reading skill test score understanding and the score of the exsposition for writing the text exsposition. There are two instruments for this research, namely objective tests to measure reading skills, comprehensionÂ and performance tests to measure the exsposition for writing text skills. Based on the results of this study, it was concluded that there was a significant correlation between reading skills, text comprehension, and exsposition writing skills in class VIII students of SMP Negeri 32 Padang. at the real level (Î±) of 95% with n-1 freedom degrees in other words if the reading skills of students 'exsposition text comprehension are good, then students' writing skills are also good. Conversely, if the reading skills of students 'exsposition text comprehension are bad then the students' writing exsposition text skills are also bad.Â Kata Kunci: Membaca Pemahaman, Keterampilan Menulis Teks, Eksposisi